2016
DOI: 10.1523/jneurosci.4614-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Regulation of hnRNPA2/B1 Translation by M1 Muscarinic Receptors

Abstract: Cholinergic vulnerability, characterized by loss of acetylcholine (ACh), is one of the hallmarks of Alzheimer's disease (AD). Previous work has suggested that decreased ACh activity in AD may contribute to pathological changes through global alterations in alternative splicing. This occurs, at least partially, via the regulation of the expression of a critical protein family in RNA processing, heterogeneous nuclear ribonucleoprotein (hnRNP) A/B proteins. These proteins regulate several steps of RNA metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Alternatively, increased VAChT expression may have long‐term effects in gene expression as we previously observed (Kolisnyk et al . ). This may also contribute to the profound morphological changes we detected in these cholinergic interneurons as discussed below.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternatively, increased VAChT expression may have long‐term effects in gene expression as we previously observed (Kolisnyk et al . ). This may also contribute to the profound morphological changes we detected in these cholinergic interneurons as discussed below.…”
Section: Discussionmentioning
confidence: 97%
“…For example, ChAT–ChR2 mice have increased levels of hnRNPA2/B1, an essential splicing regulator (Kolisnyk et al . ). However, although these abnormalities in gene expression in targeted tissues and behavioral functions are now documented, whether VAChT over‐expression can have long‐term consequences for cholinergic neuron function is unknown.…”
mentioning
confidence: 97%
“…Also, it is possible that increased latency to respond observed in the PVD-R may reflect a decrease in motivation. Further studies using more sensitive methods to investigate dopamine release, such as microdialysis in freely moving mice (39), in vivo voltammetry (17), or in vivo dopaminergic fluorescence sensors (103,104), as well as behavioral tasks interrogating motivation would be necessary to determine the influence of dopamine in these VAChTmutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in VAChT expression and function have a direct influence on the amount of ACh released from nerve terminals (17,18,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Notably, decreased VAChT expression affects cholinergic signaling (17,18,20,23,25,26,30,31,36,37,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), suggesting that VAChT is the unique transporter for ACh. Importantly, VAChT deletion disturbs ACh storage and release but does not kill cholinergic neurons (25,26,38).…”
mentioning
confidence: 99%
“…In contrast to what we observed with N-terminal TDP43, there was no reciprocal activity-dependent change in C-terminal TDP43 abundance or localization by immunocytochemistry, and we failed to observe any differences in C-terminally labeled TDP43-D2 upon addition of TEA or TTX, arguing against a cleavage event. However, previous studies demonstrated that neuronal activity regulates the abundance of similar RNA-binding proteins through alternative splicing (57,58). We therefore considered the possibility that activity gives rise to distinct TDP43 isoforms through alternative splicing.…”
Section: Tdp43 Is Regulated By Neuronal Activitymentioning
confidence: 99%